2019
DOI: 10.1038/s41380-018-0306-z
|View full text |Cite
|
Sign up to set email alerts
|

Complement pathway changes at age 12 are associated with psychotic experiences at age 18 in a longitudinal population-based study: evidence for a role of stress

Abstract: The complement cascade is a major component of the immune defence against infection, and there is increasing evidence for a role of dysregulated complement in major psychiatric disorders. We undertook a directed proteomic analysis of the complement signalling pathway (n = 29 proteins) using data-independent acquisition. Participants were recruited from the UK avon longitudinal study of parents and children (ALSPAC) cohort who participated in psychiatric assessment interviews at ages 12 and 18. Protein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 82 publications
(128 reference statements)
2
37
1
Order By: Relevance
“…Some patients in the non-psychiatric group had high plasma levels of C3bc, and we cannot exclude that these children may develop psychiatric disorders later in life. In a longitudinal population-based study, Föcking et al demonstrated that complement pathway changes at age 12 are associated with psychotic experiences at age 18 [43]. Therefore, there is a need for a follow-up longitudinal study to investigate the role of complement activation in psychiatric disorders in childhood and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients in the non-psychiatric group had high plasma levels of C3bc, and we cannot exclude that these children may develop psychiatric disorders later in life. In a longitudinal population-based study, Föcking et al demonstrated that complement pathway changes at age 12 are associated with psychotic experiences at age 18 [43]. Therefore, there is a need for a follow-up longitudinal study to investigate the role of complement activation in psychiatric disorders in childhood and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these examples, complement gene expression more broadly has been linked to superior frontal cortex thickness in healthy humans, which has been linked to general intelligence in previous studies . Furthermore, in a proteomic analysis of the complement signaling pathway using longitudinal population‐based data, individuals who went on to experience psychotic like experience were found to have upregulation of multiple complement proteins …”
Section: Introductionmentioning
confidence: 91%
“…Examples of other complement function related genes that have been associated with both SZ risk and cognition include Cub and Sushi Multiple Domains-1 (CSMD1), complement factor H (CFH), and complement C3b/C4b receptor 1 (CR1). 3,[13][14][15] In patients with SZ and health participants, we previously reported that a GWAS-identified SZ risk variant within CSMD1, which encodes for a regulator of complement, was associated with poorer general cognitive ability and episodic memory function. 8 Other variants within CSMD1 gene have also been associated with poorer cognitive performance in large samples of healthy participants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method allows the study of the relationship of two multivariate datasets, for instance, the relationship between specific lipids and proteins within the same individuals (41) . Quantitative data, derived from DIA analysis, on the broad family of complement pathway proteins were also available on these same subjects (42) , and these data were available for integrative analysis. Regularization parameters were estimated by means of a leave-one-out cross-validation.…”
Section: Methodsmentioning
confidence: 99%